Valley polarization of exciton–polaritons in monolayer WSe2 in a tunable microcavity. Issue 19 (7th May 2019) - Król, Mateusz; Lekenta, Katarzyna; Mirek, Rafał; Łempicka, Karolina; Stephan, Daniel; Nogajewski, Karol; Molas, Maciej R.; Babiński, Adam; Potemski, Marek; Szczytko, Jacek; Piętka, Barbara
Abstract : Strong light–matter interaction between cavity photons and excitons in monolayer WSe2 with spin selective excitation is demonstrated. Abstract : Monolayer transition metal dichalcogenides, known for exhibiting strong excitonic resonances, constitute a very interesting and versatile platform for the investigation of light–matter interactions. In this work, we report on a strong coupling regime between excitons in monolayer WSe2 and photons confined in an open, voltage-tunable dielectric microcavity. The tunability of our system allows us to extend the exciton–polariton state over a wide energy range and, in particular, to bring the excitonic component of the lower polariton mode into resonance with other excitonic transitions in monolayer WSe2 . We can retain up to 40% of initial circular polarization of the laser or loose it completely if polariton modes are brought into resonances with low energy excitonic modes.